Ticagrelor versus clopidogrel in patients with acute coronary syndromes intended for non-invasive management: substudy from prospective randomised PLATelet inhibition and patient Outcomes (PLATO) trial - James, Stefan; Roe, Matthew T.; Cannon, Christopher P.; Cornel, Jan H.; Horrow, Jay; Husted, Steen; Katus, Hugo; Morais, Joao; Steg, Ph Gabriel; Storey, Robert F.; Stevens, Susanna; Wallentin, Lars; et al. (The BMJ, 2011)
Objective: To evaluate efficacy and safety outcomes in patients in the PLATelet inhibition and patient Outcomes (PLATO) trial who at randomisation were planned for a non-invasive treatment strategy. - Design: Pre-specified analysis of pre-randomisation defined subgroup of prospective randomised clinical trial. - Setting 862 centres in 43 countries. - Participants: 5216 (28%) of 18 624 patients admitted to hospital for acute coronary syndrome who were specified as planned for non-invasive management. - Interventions: Randomised treatment with ticagrelor (n=2601) versus clopidogrel (2615). - Main outcome measurements: Primary composite end point of cardiovascular death, myocardial infarction, and stroke; their individual components; and PLATO defined major bleeding during one year. - Results: 2183 (41.9%) patients had coronary angiography during their initial hospital admission, 1065 (20.4%) had percutaneous coronary intervention, and 208 (4.0%) had coronary artery bypass surgery. Cumulatively, 3143 (60.3%) patients had been managed non-invasively by the end of follow-up. The incidence of the primary end point was lower with ticagrelor than with clopidogrel (12.0% (n=295) v 14.3% (346); hazard ratio 0.85, 95% confidence interval 0.73 to 1.00; P=0.04). Overall mortality was also lower (6.1% (147) v 8.2% (195); 0.75, 0.61 to 0.93; P=0.01). The incidence of total major bleeding (11.9% (272) v 10.3% (238); 1.17, 0.98 to 1.39; P=0.08) and non-coronary artery bypass grafting related major bleeding (4.0% (90) v 3.1% (71); 1.30, 0.95 to 1.77; P=0.10) was numerically higher with ticagrelor than with clopidogrel. - Conclusions: In patients with acute coronary syndrome initially intended for non-invasive management, the benefits of ticagrelor over clopidogrel were consistent with those from the overall PLATO results, indicating the broad benefits of P2Y12 inhibition with ticagrelor regardless of intended management strategy. - Trial registration Clinical trials NCT00391872.
Gesehen am 04.07.2022